Associations of physical activity and mental well-being with resilience in patients with heart failure: a cross-sectional - Kristinawati, Beti; Arifudin, Navian Fauzi; Latiifah, Itsnaani Rahmadita Nur; Pratama , Rafi Abrar (Universitas Airlangga, 2025)
Introduction: Heart failure is a common chronic condition that significantly impairs the physical and mental well-being of individuals impacted. Resilience is a dynamic occurrence involving constructive responses to adversity. The researcher aims to investigate the relationship between physical activity and mental health on resilience in heart failure patients. Methods: This study employed a quantitative, cross-sectional design. The population comprised 186 patients with heart failure at the cardiac outpatient department of Surakarta Regional General Hospital. A total of 140 participants were selected from this population using purposive sampling, based on specific criteria. The dependent variable is resilience, and the independent variables are physical activity and mental well-being. The data were gathered through the Adult Resilience Measure-Revised (ARM-R), the Mental Health Questionnaire incorporating the Depression, Anxiety, Stress Scale (DASS-42), and the Physical Activity Questionnaire derived from the International Physical Activity Questionnaire-Short Form (IPAQ-SF). The analyses used were the chi-square test and multiple linear regression analysis. Results: This study found a weak, positive relationship between mental well-being, physical activity, and resilience, with a combined R-value of 0.355. The R² value of 0.126 indicates that mental well-being and physical activity together account for 12.6% of the variance in resilience. The remaining 87.4% of the variance is due to other undetermined factors. Conclusions: Physical activity and mental well-being are positively, though weakly, related to resilience in heart failure patients. Both still contribute to improving resilience. Therefore, rehabilitation programs combining moderate physical activity and psychological support are recommended to enhance resilience and quality of life.